Decades of emerging infectious disease, food safety, and antimicrobial resistance response in Vietnam: The role of One Health - Hung Nguyen-Viet; Lam, S.; Huong Nguyen-Mai; Dao Thu Trang; Vu Thi Phuong; Nguyen Do Anh Tuan; Dang Quang Tan; Nguyen Thu Thuy; Dang Thuy Linh; Phuc Pham-Duc (Elsevier, 2022)
Since facing outbreaks of severe acute respiratory syndrome and avian influenza A in 2003, Vietnam has increasingly applied a One Health approach to address emerging infectious diseases of animal origin. Here, we reflect on the challenges and opportunities of One Health in the context of zoonoses, food safety, and antimicrobial resistance, drawing on a stocktake of One Health training, policy, and research in Vietnam. We also report on the results of a virtual consultation workshop held on July 2021 with representatives from 32 institutions in Vietnam to explore future One Health directions. As Vietnam approaches nearly two decades of disease preparedness and response, we hope our experiences can provide practical insights to support countries in developing coordination mechanisms and moving the One Health agenda forward toward better public health outcomes.